Drosophila As a Genetically Tractable Model for Social Insect Behavior - Camiletti, Alison L.; Thompson, Graham J. (Frontiers in Ecology and Evolution, 2016)
The relatively simple communication, breeding, and egg-making systems that govern reproduction in female Drosophila retain homology to eusocial species in which these same systems are modified to the social condition. Despite having no parental care, division of labor, or subfertile caste, Drosophila may nonetheless offer a living test of certain sociobiological hypotheses framed around gene function. In this review, we make this case, and do so around the recent discovery that the non-social fly, Drosophila melanogaster, can respond to the ovary-suppressing queen pheromone of the honey bee Apis mellifera. Here, we first explain the sociobiological imperative to reconcile kin theory with molecular biology, and qualify a potential role for Drosophila. Then, we offer three applications for the fly-pheromone assay. First, the availability and accessibility of massive mutant libraries makes immediately feasible any number of open or targeted gene screens against the ovary-inhibiting response. The sheer tractability of Drosophila may therefore help to accelerate the search for genes in pheromone-responsive pathways that regulate female reproduction, including potentially any that are preserved with modification to regulate worker sterility in response to queen pheromones in eusocial taxa. Secondly, Drosophila's powerful Gal4/UAS expression system can complement the pheromone assay by driving target gene expression into living tissue, which could be well-applied to the functional testing of genes presumed to drive ovary activation or de-activation in the honey bee or other eusocial taxa. Finally, coupling Gal4 with UAS-RNAi lines can facilitate loss-of-function experiments against perception and response to the ovary inhibiting pheromone, and do so for large numbers of candidates in systematic fashion. Drosophila's utility as an adjunct to the field of insect sociobiology is not ideal, but retains surprising potential.